Правове регулювання опозиційної діяльності в Україні: постановка проблеми - Берназюк, І.М. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
The article is dedicated to the study of the constitutionally-legal adjusting of opposition activity in Ukraine. It is also proved in the article, that the constitutionally-legal adjusting necessarily must head for regulation of opposition activity of such subjects as: to parliamentary opposition; opposition Cabinet of Ministers in Ukraine; oppositions are in local advices.